Abnormal band bowing effects in phase instability crossover region of GaSe1-x Te x nanomaterials - Hui Cai (Nature Portfolio, 2018)
Alloys of two-dimensional materials normally occur when two components crystallize in the same phase. Here, the authors observe an anomalous phase instability, accompanied by a band bowing effect, in GaSe1-x Te x alloys on GaAs(111).